Implementasi Pembelajaran Berbasis Alam sebagai Sarana Pengembangan Karakter Sosial Peserta Didik di Sanggar Anak Alam - Ayuni Febiana, Atika; Mujib, Muhammad Yazid Fatkhul; ahriza Davina Putri, Cony; Hidayatusholiha, Alvi; Aprilia, Popy; Muhtarom, Taufik (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study examines the implementation of Nature-Based Learning (NBL) at Sanggar Anak Alam (SALAM) as a means of developing students' social character. A descriptive qualitative method was used, with data collection techniques including observation, interviews, and documentation. The subjects of the study were 15 students selected purposively. The results showed that NBL was implemented through project-based activities, inclusive interactions, and regular reflections, effectively shaping students' responsibility, empathy, and environmental awareness. Despite challenges such as limited facilities and a lack of teaching method variation, curriculum innovation and community involvement helped address these issues. The findings emphasize that NBL not only enhances academic skills but also social character, making it a relevant and applicable holistic education model